2015
DOI: 10.1371/journal.pone.0145369
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma in Gorlin’s Patients: a Matter of Fibroblasts-Led Protumoral Microenvironment?

Abstract: Basal cell carcinoma (BCC) is the commonest tumor in human. About 70% sporadic BCCs bear somatic mutations in the PATCHED1 tumor suppressor gene which encodes the receptor for the Sonic Hedgehog morphogen (SHH). PATCHED1 germinal mutations are associated with the dominant Nevoid Basal Cell Carcinoma Syndrome (NBCCS), a major hallmark of which is a high susceptibility to BCCs. Although the vast majority of sporadic BCCs arises exclusively in sun exposed skin areas, 40 to 50% BCCs from NBCCS patients develop in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
3
6
0
Order By: Relevance
“…The cellular provenance of CXCL14 is unclear: while Hh ligands are conventionally thought to derive from epithelial cells and act on mesenchymal cells, CXCL14 protein and gene expression appear to localise to epithelial regions (figure 4). However, there is evidence for nuclear GLI1 and GLI2 localisation in both epithelium and fibroblasts in IPF,5 while other studies have shown Hh pathway activation in both epithelium and mesenchymal cells in lung adenocarcinoma,52 BCC53 and taste bud papillae,54 all dependent on epithelial-mesenchymal interactions.…”
Section: Discussionmentioning
confidence: 98%
“…The cellular provenance of CXCL14 is unclear: while Hh ligands are conventionally thought to derive from epithelial cells and act on mesenchymal cells, CXCL14 protein and gene expression appear to localise to epithelial regions (figure 4). However, there is evidence for nuclear GLI1 and GLI2 localisation in both epithelium and fibroblasts in IPF,5 while other studies have shown Hh pathway activation in both epithelium and mesenchymal cells in lung adenocarcinoma,52 BCC53 and taste bud papillae,54 all dependent on epithelial-mesenchymal interactions.…”
Section: Discussionmentioning
confidence: 98%
“…Functional dermo-epidermal interaction in 3D organic cultures evidenced reduced epidermal thickness and dysregulation of keratinocyte differentiation proteins when healthy keratinocytes were maintained in the presence of NBCCS fibroblasts [105]. In the same experimental system, diffusible factors produced by NBCCS fibroblasts strongly stimulate the expression of p53 in an organotypic in vitro model containing normal keratinocytes, whereas carcinoma cells carrying mutate p53 acquired an invasive phenotype in the presence of NBCCS dermis [106]. The possible contribute of syndromic dermal cells in photodynamic therapy success has also been highlighted demonstrating that GS fibroblasts are predisposed to accumulate UV-dependent oxidative stress and consequence cell death [106].…”
Section: Dermal Fibroblasts From Gorlin Syndrome Have Phenotypic Traimentioning
confidence: 93%
“…In the same experimental system, diffusible factors produced by NBCCS fibroblasts strongly stimulate the expression of p53 in an organotypic in vitro model containing normal keratinocytes, whereas carcinoma cells carrying mutate p53 acquired an invasive phenotype in the presence of NBCCS dermis [106]. The possible contribute of syndromic dermal cells in photodynamic therapy success has also been highlighted demonstrating that GS fibroblasts are predisposed to accumulate UV-dependent oxidative stress and consequence cell death [106]. In addition to an abnormal response to UV, NBCCS fibroblasts display increased oxidative perturbation following radiation associated with a marked deficiency in aldehyde dehydrogenase 1A1, one of the rate-limiting enzymes in retinoic acid synthesis [105].…”
Section: Dermal Fibroblasts From Gorlin Syndrome Have Phenotypic Traimentioning
confidence: 99%
“…Cancer cells can activate their stroma and trigger the remodeling of extracellular matrix (ECM) promoting tumor growth. Moreover, the tumor microenvironment can also generate oxidative damage and genetic instability, stimulating invasive capacity of cancer cells [ 19 21 ]. In this context, dermal fibroblasts obtained from skin biopsies of patients with XP or GS syndromes would be a key determinant in investigating factors involved in the malignant progression and spread of skin cancer and could represent an important target for novel cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have also assessed whether the effects of MAL-PDT were sustained when these fibroblasts were stimulated with UVA and UVB light at sub-genotoxic doses. It can be expected that XP and GS fibroblasts show characteristics of cancer-associated fibroblasts (CAFs), playing an important role in several aspects of the tumor progression, promoting cancer cell growth, invasiveness and angiogenesis [ 19 , 22 , 23 ], so they could be excellent potential targets for PDT to prevent the appearance of skin cancer in XP and GS patients.…”
Section: Introductionmentioning
confidence: 99%